UJI JENIS NUTRISI PADA SELADA HIDROPONIK SISTIM WICK: Nutrition Type Test On Hydroponic Lettuce Wick System - Ratna Santi; Siti Khodijah Nyayu (AgriPeat, 2022)
Simple hydroponic wick system (Wicks) can be applied in overcoming the land crisis for the development of horticultural crops. Nutrients are an important part of hydroponic activities and Abmix is ​​a standard nutrient in hydroponic farming activities. It is necessary to test the opportunities for the utilization of nutrients from POC and synthetic fertilizers. This study aims to determine the opportunities for using liquid organic fertilizers (POC) and synthetic fertilizers in hydroponic lettuce plants using the wick system. The treatment consisted of 5 types of nutrition, namely (1) AB mix (control) 50 mL per 10 liters of water (ABM); (2) NPK 10 g + Gandasil 5 g per 10 liters of water (NPG); (3) Abmix 25 mL + 5g NPK + 2.5 g Gandasil per 10 liters of water (ANG); (4) Abmix 25 mL + 400 mL POC from chicken feather waste (ABP) and (5) 5 g NPK + 2.5 g Gandasil + 400 mL POC chicken feathers per 10 liters of water (NGP). The results showed that there were differences in the growth of lettuce in the hydroponic wick system due to the type of nutrition treatment. Alternative nutrients that have the potential to be used in wick cystic hydroponic lettuce are Abmix 25ml + 5g NPK + 2.5 g Gandasil per 10 liters of water (ANG) and Abmix 25 mL+ 400 mL POC from chicken feather waste per 10 liters of water (ABP)